A measure of reliability for scientific co-authorship networks using fuzzy logic - de Oliveira, Sandra Cristina [UNESP]; Cobre, Juliana; Pereira, Danilo Florentino [UNESP] (Springer Nature, 2021)
Studies on the reliability of scientific co-authorship networks identify whether they are reliable, according to their researchers’ participation and how strong the co-authorship relationships are. Co-authorship among members of a research group can usually be represented by a graph in which each node represents one of the researchers belonging to this group, and each edge represents a connection (co-authorship relationship) between two researchers. The aim of this investigation is to propose a mathematical analysis using fuzzy logic to estimate the reliability of scientific co-authorship networks, based on node centrality measures and the existence of uncertainties in estimating the reliability of the individual components (researchers). To develop the proposed methodology, a research group from São Paulo State University–UNESP registered with the National Council for Scientific and Technological Development (CNPq) in Brazil was analysed. The results show the simplicity of implementation and the viability of mathematical modelling to estimate the reliability of scientific co-authorship networks.
Keywords: Fuzzy systems; Network reliability; Networks; Scientific collaboration; Social networks